2019
DOI: 10.1038/s41467-019-08757-2
|View full text |Cite
|
Sign up to set email alerts
|

High-speed mechano-active multielectrode array for investigating rapid stretch effects on cardiac tissue

Abstract: Systematic investigations of the effects of mechano-electric coupling (MEC) on cellular cardiac electrophysiology lack experimental systems suitable to subject tissues to in-vivo like strain patterns while simultaneously reporting changes in electrical activation. Here, we describe a self-contained motor-less device (mechano-active multielectrode-array, MaMEA) that permits the assessment of impulse conduction along bioengineered strands of cardiac tissue in response to dynamic strain cycles. The device is base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…Indeed, the main field is confined within the actuation membrane, whilst the fringe field is not expected to impact the cell culture, due to the geometry of the device. In any case, it is useful to consider that previous studies on DEA-based cell stretchers, which have exposed cells to high fringe fields, have not obtained evidence of any effect on cellular (cardiomyocytes) viability (Imboden et al, 2019).…”
Section: Future Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the main field is confined within the actuation membrane, whilst the fringe field is not expected to impact the cell culture, due to the geometry of the device. In any case, it is useful to consider that previous studies on DEA-based cell stretchers, which have exposed cells to high fringe fields, have not obtained evidence of any effect on cellular (cardiomyocytes) viability (Imboden et al, 2019).…”
Section: Future Developmentsmentioning
confidence: 99%
“…In particular, within the family of electromechanically active polymers (Carpi, 2016), dielectric elastomer actuators (DEAs) at present can in general offer large strains (10-100%) and relatively high stresses (up to 1 MPa) in response electrical stimuli, with simple structure, compact size, light weight, and low power consumption (Pelrine et al, 2000;Carpi et al, 2008). Due to these attractive properties, their potential also for the mechano-stimulation of cells has recently been explored (Akbari and Shea, 2012a,b;Cei et al, 2016;Poulin et al, 2016Poulin et al, , 2018Imboden et al, 2019). However, so far, they have been used for cell stretching of planar (uni-or bi-directional, or radial) and uniform kind.…”
Section: Introductionmentioning
confidence: 99%
“…With further processing, these planar structures can be transformed into bending actuators, rolled actuators, or prestrained systems using rigid frames . For many applications of interest, contractile actuation is advantageous . Yet prestrained DEAs provide contractile strains in only a small proportion of the total device area .…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, the actuator that can generate alternately tensile and compression strains was proposed by Poulin et al [78]. Afterward, as the newest work, for the purpose of investigating drastic cases like rapid stretch effect on cardiac tissue, Imboden et al [85] showed their high-speed mechano-active multielectrode actuator, which can provide stimulus of mechanoelectrical coupling mechanism. Such a progress actually indicates the diversified future of the DEA-based bioreactor.…”
Section: Dea-based Bioreactor For Small Population Of Cellsmentioning
confidence: 99%